The Pediatric Upper Extremity - Abzug, Joshua M.; Kozin, Scott H.; Zlotolow, Dan A.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2015)
Sub-specialization within pediatric orthopedics is growing, in part due to the development of free-standing children's hospitals and the desire by patients and their parents to have "experts" care for them. We are at the forefront of a trend in physicians classifying themselves as pediatric upper extremity surgeons. Numerous pediatric hospitals now have or are recruiting physicians to focus their practice in this area. Historically, these issues were treated by general orthopedic surgeons, adult hand surgeons, pediatric orthopedic surgeons, or plastic surgeons. However, none of these professionals treat the entirety of pediatric upper extremity pathology, and no single reference has focused on the treatment of the pediatric upper extremity as a whole. For example, fractures have typically been written about in pediatric textbooks, while tendon and nerve injuries are covered in adult hand textbooks. This textbook is a comprehensive, illustrated reference that discusses all aspects of the pediatric upper extremity, from embryology and functional development to nerve injuries, trauma, tumors, burns, sports injuries and more.
I: DEVELOPMENT -- Embryology -- Functional development -- II: PHYSICAL EXAMINATION -- Physical examination -- Outcome measures -- III: IMAGING -- IV: ANESTHESIA -- V: OCCUPATIONAL THERAPY -- Splinting and casting -- Occupational therapy evaluation and treatment -- VI: CONGENITAL DIFFERENCES -- Introduction to congenital differences and genetics -- Failure of formation -- Failure of differentiation -- Duplication -- Overgrowth -- Undergrowth -- Constriction band syndromes -- Metabolic and endocrine abnormalities -- Genetic syndromes -- Skeletal dysplasias -- VII: NERVE -- Nerve anatomy and diagnostic evaluation -- Ulnar nerve injury -- Median nerve injury -- Radial nerve injury -- VIII: BRACHIAL PLEXUS PALSY -- Obstetrical brachial plexus palsy -- Microsurgery for obstetrical brachial plexus birth palsy -- Glenohumeral joint secondary procedures -- Elbow flexion secondary procedures -- Traumatic brachial plexus injuries -- IX: TETRAPLEGIA -- Introduction to tetraplegia -- Treatment -- X: NEUROMUSCULAR: Cerebral palsy -- Arthrogryposis -- XI: TRAUMA -- Multiply injured child -- Non-accidental trauma -- Nail bed injuries -- Flexor tendon injuries -- Extensor tendon injuries -- Amputations/replantation -- Phalangeal fractures -- Metacarpal fractures -- Hand dislocations -- Carpal fractures -- Distal radius fractures -- Forearm fractures -- Monteggia fracture dislocations -- Galeazzi and Essex Lopresti injuries -- Pediatric elbow and supracondylar fractures -- Distal articular humerus fractures -- Medial epicondyle fractures, elbow dislocations, and transphyseal separations -- Radial head, neck and olecranon fractures -- Proximal humerus and humeral shaft fractures -- Clavicle fractures, AC dislocations, SC dislocations and scapula fractures -- XII: INFECTIONS -- Hand infections -- Cellulitis and necrotizing fasciitis -- Osteomyelitis and septic arthritis -- XIII: TUMORS -- Benign soft tissue lesions -- Benign bony lesions -- Malignant lesions -- XIV: COMPARTMENT SYNDROME -- XV: SKIN LESIONS -- Congenital lesions -- Acquired lesions -- XVI: BURNS -- XVII: VASCULAR DISORDERS -- XVIII: RHEUMATOLOGIC DISORDERS -- XIX: FACTITIOUS DISORDERS -- XX: SPORTS INJURIES -- Caring for the athlete -- The throwing athlete -- The gymnast -- XXI: ARTHROSCOPY -- Wrist -- Elbow -- Shoulder -- XXII: OTHER TOPICS -- Trigger digits -- Kienbock's disease -- Madelung's deformity -- Torticollis and Sprengel's deformity -- Multi-ligamentous laxity -- Thoracic outlet syndrome -- Prostheses.
Keywords: Medicine; Orthopedics; Pediatrics; Medicine & Public Health; Orthopedics; Pediatrics; Surgical Orthopedics; Electronic books